Identificação de crianças precoces com indicadores de altas habilidades/superdotação pelos familiares e suas expectativas - Oliveira, Elaine Cristina Batista Borges de [UNESP] (2014)
The family is an institution in motion in their organization, and first instance in the formation of its members. Take in the family a child early requires knowledge and ability to identify it and understand it, the manifestations of the precocity initially appear in the family context, which often do not have the necessary conditions to develop and meet the challenges of educating a child early. In this context in which early children can be a cause of family conflicts is that there is an urgent need to investigate how parents or guardians identify the precocity and what expectations have on these children. The aim of this work was to analyze how the parents and/or guardians identify precocities in their children, as well as the expectations generated in them, and check how they perceive the changes in family dynamics, in function of the precocity. This research used two questionnaires that were answered by 19 participants. The data were analyzed in two stages, the first through the analysis and discussion of the Questionnaire for the Identification of Indicators of High Abilities/Gifted - Responsible (QUIIAHSD - R) de Freitas and Perez (2012) adapted to analyze situations that would confirm the existence of indicators of precocity in the aspects of physical development, academic and social child and the second based on questionnaire responses of open questions and organized according to a content analysis of Bardin (1977), submitted from four major categories: 1. the concept of precocity; 2. moment of perception of the precocity; 3. opinion on the presence of a child early; 4. expectations. It was found that the process of identification of children with early indicators of high ability/gifted students is complex and includes many variables, but that the parents and/or guardians are also able to identify the precocity in children, regardless of daily coexistence or the knowledge you have about the subject, because they identify on the...